Electrochemical (Bio)Sensors for Toxins, Foodborne Pathogens, Pesticides, and Antibiotics Detection: Recent Advances and Challenges in Food Analysis - Marta Feroci; Gerardo Grasso; Roberto Dragone; Antonella Curulli (Biosensors, 2025)
Food safety plays an important and fundamental role, primarily for human health and certainly for the food industry. In this context, developing efficient, highly sensitive, safe, inexpensive, and fast analytical methods for determining chemical and biological contaminants, such as electrochemical (bio)sensors, is crucial. The development of innovative and high-performance electrochemical (bio)sensors can significantly support food chain monitoring. In this review, we have surveyed and analyzed the latest examples of electrochemical (bio)sensors for the analysis of some common biological contaminants, such as toxins and pathogenic bacteria and chemical contaminants, such as pesticides, and antibiotics.